ISLAM ON AL-ATTAS AND WILFRED C SMITH PERSPECTIVE (Analysis Study on The Meaning of Islamic Religion) - Jarman Arroisi; Minhajul Afkar (Universitas Darussalam Gontor, 2020)
This article discusses to find out deeply Al-Attas and Smith perspective on understanding Islam, which are both of them have defferences worldview on understanding a reality. Al-Attas as a muslim scholar who respearhead Islamic worldview in this modern era has a differences perspective with Smith as a orientalist and a pioneer of world theology concept which is all of his thought based on Western worldview. The analysis focuses to theological aspect that is rooted of problem on Islamic concept according to them. Based on the analysis could be reached that Al-Attas said that Islam is a word that is directly chosen by Allah to describe the meaning of religion, and necessitates to all Muslims did all the sharī’ah created by Allah SWT both in the pillars of Islam and other teachings contained in the al-Qur'an and Hadith, and underlying it all with faith against God. While Smith refers to Islam only as a word that means submission and applies to all mankind where all can be referred to as Muslims if they commit surrender to their God without looking at their worship. It all resulted in the emergence of the understanding of religious pluralism in which all religions are the same to teach a goodness.